METHODS OF TEACHING TYPES OF WORDS ACCORDING TO THE RELATIONSHIP OF FORM AND MEANING - Xayrullayeva R. L (European Science Publishing, 2024)
This article shows the ways of understanding the word, understanding its meaning and correct use in the native language of schoolchildren. provides information on ways to expand the worldview of students by increasing vocabulary.
Keywords: word, word meaning, reader's dictionary, synonymy of words, antonymy of words, semantic aspects of words, sarcastic meaning of words, phraseological units, polysemy of words, figurative meaning, figurative words, figurative meaning of words, text, proverb text.